Enhancing Palliative Care Accessibility Through Puskesmas: Insights from Rural and Coastal Communities in Indonesia - Agussalim; Rustam Ajie; Mustamin; Muhammad Nur; Hikmawati Mas’ud; Lydia Fanny (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: The strong influence of Eastern culture in Indonesia has led to an uneven distribution of palliative patient services and an increasing number of difficult-to-cure diseases such as cancer and AIDS. Aim: To gather information from the community about the implementation and availability of palliative services. Material and Method: Qualitative research was conducted with the help of various interviews. Result: Providing palliative care in rural areas allows people to receive care at home with their families, in line with their cultural practices. Conclusion: The importance of preparing palliative care in rural areas, especially in poor and developing countries around the world.